Effect of gamma irradiation on the germination, pollen viability, and morpho-agronomic of Pachyrhizus erosus cv. Kota Padang (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hayati PKD, Witari S, Rozen N, Sutoyo, Widiarsih S. 2022. Effect of gamma irradiation on the germination, pollen viability, and morpho-agronomic of Pachyrhizus erosus cv. Kota Padang. Biodiversitas 23: 1231-1238. Yam bean or Pachyrhizus erosus (L.) Urb., an unexploited plant that produces the storage root tuber, is used in a variety scale of food processing and cosmetic industries in Indonesia. Novel approaches to induce variability in yam bean cv. Kota Padang will accelerate the breeding efforts and improvement of the cultivar. The purpose of the study was to elucidate the effects of gamma irradiation on seed germinability, pollen viability, and morpho-agronomic performance of yam bean cv. Kota Padang. Seeds were irradiated with gamma-rays on 0, 100, 150, 200, 300, 400, and 500 Gy, then LD50 was determined based on the germination percentage. Observation of the irradiated yam bean growth in the field was carried out individually. Results showed that gamma irradiation decreased seed germinability, pollen viability, and agronomic traits. Still, it increased the variability of the traits among the mutant populations, except for the number of branches. Correlation analysis confirmed the results, indicating that selection in the next M2 generation must consider semi-dwarf and pod yield performances. The LD50 was 150 and 176 Gy; hence, the irradiation doses of 150 and 200 Gy were appropriate in producing high genetic diversity with low physical damage in yam bean cv. Kota Padang.
Keywords: Bengkuang, correlation, LD50, pollen fertility, variability